THE INFLUENCE OF TIKTOK CONTENT ON DIGITAL MARKETING OF ELECTRONIC PRODUCTS ON E-COMMERCE: A SYSTEMATIC LITERATURE REVIEW - Mochamad Rizal Yulianto; Akhmad Nur Mubarok; Muhammad Suyogo; Alshaf Pebrianggara; Istian Kriya Almanfaluti (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to analyze the influence of TikTok content on digital marketing of electronic products in e-commerce through a systematic literature review. TikTok, as an increasingly popular social media platform, offers various engaging content features for users. This study examines how elements of content on TikTok, such as creative short videos, viral challenges, and influencer collaborations, can affect digital marketing strategies and sales performance of electronic products on e-commerce platforms. The methodology used is systematic literature review (SLR) by gathering and analyzing various relevant previous studies on the topic. The findings of this review indicate that TikTok content has a significant impact on brand awareness, consumer engagement, and sales conversion. Effective marketing strategies implemented on TikTok can increase product exposure, attract consumer attention, and drive purchasing decisions. These findings provide valuable insights for digital marketing practitioners in leveraging social media platforms to enhance the marketing performance of electronic products in e-commerce.